Microbiota Associated With Ototyphlonemertes Species (Nemertea, Hoplonemertea, Monostilifera, Ototyphlonemertidae) Reveal Evidence of Phylosymbiosis - Francesca Leasi; Ester M. Eckert; Jon L. Norenburg; W. Kelley Thomas; Joseph L. Sevigny; Jeffrey A. Hall; Herman H. Wirshing; Diego Fontaneto (Ecology and Evolution)
ABSTRACT Phylosymbiosis, the association between the phylogenetic relatedness of hosts and the composition of their microbial communities, is a widespread phenomenon in diverse animal taxa. However, the generality of the existence of such a pattern has been questioned in many animals across the tree of life, including small‐sized aquatic invertebrates. This study aims to investigate the microbial communities associated with poorly known marine interstitial nemerteans to uncover their microbiota diversity and assess the occurrence of phylosymbiosis. Specimens from various Central American sites were analyzed using morphology‐based taxonomy and molecular techniques targeting the host 18S rRNA gene whereas their microbial association was analyzed by targeting the prokaryotic 16S rRNA gene. Phylogenetic and statistical analyses were conducted to examine the potential effects of host nemertean taxa and sampling locations on the host‐associated microbial communities. The results provide compelling evidence of phylosymbiosis in meiofaunal nemertean species, highlighting the significant impact of host genetic relatedness on microbiome diversity in small‐sized animals. This finding supports previous studies that demonstrate how certain nemertean species harbor distinct microbial communities with functional and ecological implications. Given the remarkable diversity of meiofaunal animals—spanning numerous phyla with varying lifestyles and co‐existing in the same habitat—combined with advancements in multi‐omics approaches, there is a promising opportunity to deepen our understanding of the evolutionary and ecological interactions between hosts and their microbiota throughout the animal tree of life.